Nano-positioning system using self-sensing function of giant magnetostrictive actuator - Yuuki TAMURA; Hayato YOSHIOKA; Hidenori SHINNO; Hiroshi SAWANO (Nihon Kikai Gakkai ronbunshu, 2015)
A micro-scale texture generated on the surface characterizes wettability, friction and optical property of the substrates. In recent years, demands for adapting such functional surface to the large scale and complex structure have increased in a variety of industries. In general, the micro-scale texture can be generated by the ultra-precision machining process, which has high flexibility and high precision. In this study, for reduction in a lead time, in order to construct the micro structure and form a shape by milling at the same time, a non-contact positioning system driven by a giant magnetostrictive element (GME) is newly proposed. Besides, it is not possible to measure the displacement of a milling tool with a displacement sensor. Hence, this positioning system uses the GME not only as an actuator but also as a sensor simultaneously in order to estimate its displacement. As mentioned above, utilizing an actuator as a means of sensing its own displacement is referred to as a self-sensing function. Furthermore, by using estimated displacement for feedback control, hysteresis of a GME can be compensated. Therefore, this positioning system can be driven with non-contact without additional displacement sensor. From the performance evaluations, the positioning system provides high resolution and hysteresis compensation with self-sensing function.